Politik Identitas dalam Iklan Politik pada Pemilihan Kepala Daerah Sumatera Utara 2018 - Maghfira Faraidiany; Heri Kusmanto; Warjio Warjio (Universitas Negeri Medan, 2019)
In connection with general elections, the role of political advertising is very important because it is considered to be a political engine for candidates in an effort to show their existence and efforts to attract and gain support during the campaign period. The use of identity in political advertising is used to influence voters' political choices. The 2018 North Sumatra regional election was attended by two pairs of candidates who met the requirements of the KPU. They are Edy Rahmayadi and Musa Rajeck Shah who are familiarly called Ijeck (Eramas) and Djarot Saiful Hidayat and Sihar Sitorus (Djoss). The two candidates played the issue of identity together in their political advertisements. This study aims to explain what identities are used in the candidates' political advertisements. From the results of the study it can also be concluded that the issue of identity politics can still be seen from the advertisements of both pairs of candidates and they also use identity issues to increase support.